SPP REAL-TIME AND DAY-AHEAD ENERGY MARKETS - Piliposyan, T.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
Southwest Power Pool (SPP) is a regional power transmission organization in the United States. Virtual transactions on the SPP markets are sold at auction. There are Real-Time (RT) and Day-Ahead (DA) markets, where you can buy electricity by winning an auction. Virtual transactions are a valuable component of the bilateral market. All market participants have DA and RT series of prices in hourly basis. In this article, we take a large amount of data of DA and RT prices and try to see which distribution function have the returns of RT prices. Then we make a regression between DA and RT prices, to see how they are related to each other.